The socio-economic factors affecting the emergence and impacts of new genomic techniques in agriculture: A scoping review. (November 2022) - Lemarié, Stéphane; Marette, Stéphan
Abstract: Background: The development of new genomic techniques (NGTs) has the potential to address some future challenges related to food security, agroecology and global warming. NGTs encompass ZFN-1, ZFN-2 and ZFN-3 technologies, TALENs, Meganucleases, CRISPR-Cas, and Oligonucleotide directed mutagenesis. The regulation of innovations based on NGT is sensitive and debated in many countries around the world. Scope and approach: To better understand the possible consequences of NGTs and their potential applications to plant and related food production, we conduct a scoping review of the literature focusing on economic issues related to NGT. This review covers a rather recent literature, namely, published mainly over the last 5 years, and we also underline the overlooked issues. Our review leads us to present the main issues related to the consumer perception, the supply of NGT related to the research effort, the intellectual property rights and the regulation. Key findings and conclusions: The socio-economic factors affecting the emergence and impacts of new genomic techniques in agriculture are unevenly analyzed in the literature. A large part of the literature focuses on regulation issues. However, a clear understanding of both consumer preferences and supply chain organizations is also essential for understanding the possible emergence and the impact of NGT, but these issues raise less attention. We also insist on the necessity of evaluating the option value of NGT that would thwart the possible but unlikely disappearance of some conventional food productions. Highlights: Economic conditions and regulation are key drivers of the diffusion of innovation based on New Genomic Techniques (NGTs). The literature on the economic issues related to NGTs mainly cover regulation issues. Emergence and impact of NGTs also depends on consumer preferences, supply chain and intellectual property rights strategies. Overlooked questions covers the option value related to NGTs and the link between regulation and public controversies.